La cura climática en “La Montaña Mágica”, de Thomas Mann - Montiel Llorente, Luis (Anales de Hidrología Médica, 2007)
Since tuberculosis is the emblematic disease in “The Magic Mountain”, climate cure also plays a central role in the work. But, just as in the novel tuberculosis is a metaphor for other malaises of the individual and society and of the threats that overshadow them both, climate cure also acquires great symbolic value in the story. The place, the weather, the passage of time –of life– for the patients in extraordinary circumstances may, in some cases –as in that of the protagonist Hans Castorp– bring about a different type of cure that is not merely biological, but that reaches into the innermost being of the person. Thomas Mann’s skill, in any case, allows us to access both dimensions of the disease and of its treatment.